Adsorption properties of carbon nanotubes and application of thermal desoprtion spectroscopy to ammonia and methane ices and zoisite - Vasta, Roberta; Bonanno, Assunta; Falcone, Giovanni (My University, 2014)
In this work we wanted to underline the importance of Thermal Desorption Spectroscopy and its applications to several branches of Physics. Temperature-programmed desorption techniques (TPD) are important to determinate kinetic and thermodynamic parameters of desorption processes and decomposition reactions. Knowledge of the nature of the desorption process is fundamental to understand the nature of the elementary chemical processes of adsorbates, as the energetics of bonding, the specification of the chemical nature of the bound species and the nature and magnitude of interactional effect between adsorbed species. We focused our attention on the applications of Thermal Desorption Spectroscopy (TDS) to High-Energies Physics, Astrophysics and Geophysics; in fact this technique was used, respectively, to investigate the molecular hydrogen adsorption on carbon nanotubes, the effects of electron bombardment on ammonia and methane ices and changes of zoisite mineral after heating. The molecular hydrogen adsorption on carbon nanotubes was studied to find a possible solution to vacuum system problems of Large Hadron Collider (LHC); in fact, the circular path of photon beams produces synchrotron radiation which deteriorates LHC vacuum desorbing gas molecules from the ring walls. Among the desorbed species the most problematic to pump out is H2. Since LHC elements operate at low temperatures, a possible solution to vacuum problem is the installation of cryosorbent materials on the LHC walls. In this work we study the possibility to use carbon nanotubes as criosorbers in future accelerators. Our sample, furnished by Prof. Nagy group of Chemical Engineering Department of Calabria University, is constituted by MWNTs synthesized by chemical vapor deposition using C2H4 and subsequently purified. Our investigations confirm that the carbon nanotubes have a great adsorption capacity also at low temperatures both for H2 and noble gases as Kr; then we observed that H2 adsorption on CNT is described by a first kinetic-order, while Kr adsorption is characterized by a zero kinetic-order. By means of TDS we calculate the activation energy for H2 adsorption on carbon nanotubes and we found a value of about 3KJ/mol, perfectly coherent with theoretic one. Moreover, from a comparison between nanotubes and other carbon-based material (as charcoal), we noted that adsorption efficiency for CNT is almost an order of magnitude higher then charcoal. So carbon nanotubes are good candidates to cryosorbers in future accelerators. 2 As Thermal Desorption Spectroscopy application to Astrophysics we studied the effect of electron bombardment on ammonia and methane ices. The interstellar medium is composed for 99% by gas; molecules, atoms and radicals at gas state condense on dust grains surface of molecular clouds (at 10 K) creating an icy mantle with a thickness of 0.1 μm. The presence of ices is confirmed by IR spectroscopy of obscured stellar sources and in interstellar grains are localized solid mixture containing H2O, CO, CH4 and NH3. In these environments ices are subjected to chemical and physical processes, specifically to bombardment of photons and cosmic rays, with the consequent synthesis of new organic species In this work we conducted an investigation of the chemical processing of ammonia and methane ices subjected to energetic electrons. By Thermal Desorption Spectroscopy we verify the production of new organic species, after energetic irradiation in interstellar ices, as diazene (N2H2), ethane (C2H6) and acetylene (C2H2). Finally, in Geophysics and Petrology Thermal Desorption Spectroscopy can be used to study minerals chemical composition. Our interest was focused on zoisite and the sample investigated was furnished by prof. Ajò from “Institute of Inorganic Chemistry and Surfaces” of CNR, in Padova. In this work we used TDS to investigate zoisite behaviour during heating form room temperature to 650oC and to understand if its modification into tanzanite variety after heating is due to structural changes or to a dehydration mechanism.
Dottorato di Ricerca in Fisica, Ciclo XXIII, a.a. 2010-2011
Keywords: Fisica; Assorbimento; Nanotubi; Carbonio; Spettroscopia; Ammoniaca; Metano